Impact of Receiving Hospital on Out‐of‐Hospital Cardiac Arrest Outcome: Racial and Ethnic Disparities in Texas - Ryan Huebinger; Marina Del Rios; Benjamin S. Abella; Bryan McNally; Carrie Bakunas; Richard Witkov; Micah Panczyk; Eric Boerwinkle; Bentley Bobrow (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Factors associated with out‐of‐hospital cardiac arrest (OHCA) outcome disparities remain poorly understood. We evaluated the role of receiving hospital on OHCA outcome disparities. Methods and Results We studied people with OHCA who survived to hospital admission from TX‐CARES (Texas Cardiac Arrest Registry to Enhance Survival), 2014 to 2021. Using census data, we stratified OHCAs into majority (>50%) strata: non‐Hispanic White race and ethnicity, non‐Hispanic Black race and ethnicity, and Hispanic or Latino ethnicity. We stratified hospitals into performance quartiles based on the primary outcome, survival with good neurologic outcome. We evaluated the association between race and ethnicity and care at higher‐performance hospitals. We compared 3 models evaluating the association between race and ethnicity and outcome: (1) ignoring hospital, (2) adjusting for hospital as a random intercept, and (3) adjusting for hospital performance quartile. We adjusted models for possible confounders. We included 10 434 OHCAs. Hospital performance quartile outcome rates ranged from 11.3% (fourth) to 37.1% (first). Compared with OHCAs in neighborhoods of majority White race, those in neighborhoods of majority Black race (odds ratio [OR], 0.1 [95% CI, 0.1–0.1]) and Hispanic or Latino ethnicity (OR, 0.2 [95% CI, 0.2–0.2]) were less likely to be cared for at higher‐performing hospitals. Compared with White neighborhoods (30.1%) and ignoring hospital, outcomes were worse in Black neighborhoods (15.4%; adjusted OR [aOR], 0.5 [95% CI, 0.4–0.5]) and Hispanic or Latino neighborhoods (19.2%; aOR, 0.6 [95% CI, 0.5–0.7]). Adjusting for hospital as a random intercept, outcomes improved for Black neighborhoods (aOR, 0.9 [95% CI, 0.7–1.05]) and Hispanic or Latino neighborhoods (aOR, 0.9 [95% CI, 0.8–0.99]). Adjusting for hospital performance quartile, outcomes improved for Black neighborhoods (aOR, 0.8 [95% CI, 0.7–1.01]) and Hispanic or Latino neighborhoods (aOR, 0.9 [95% CI, 0.8–0.996]). Conclusions In Black and Hispanic or Latino communities, OHCAs were less likely to be cared for at higher‐performing hospitals, and adjusting for receiving hospital improved OHCA outcome disparities.